Role of Extracellular Trap Release During Bacterial and Viral Infection - Schultz, Bárbara M.; Acevedo, Orlando A.; Kalergis, Alexis M.; Bueno, Susan M. (Frontiers in Microbiology, 2022)
Neutrophils are innate immune cells that play an essential role during the clearance of pathogens that can release chromatin structures coated by several cytoplasmatic and granular antibacterial proteins, called Neutrophil Extracellular Traps (NETs). These supra-molecular structures are produced to kill or immobilize several types of microorganisms, including bacteria and viruses. The contribution of the NET release process (or NETosis) to acute inflammation or the prevention of pathogen spreading depends on the specific microorganism involved in triggering this response. Furthermore, studies highlight the role of innate cells different from neutrophils in triggering the release of extracellular traps during bacterial infection. This review summarizes the contribution of NETs during bacterial and viral infections, explaining the molecular mechanisms involved in their formation and the relationship with different components of such pathogens.